A comparative study of saffron aqueous extract and its active ingredient, crocin on the in vitro maturation, in vitro fertilization, and in vitro culture of mouse oocytes - Elham Mokhber Maleki; Hussein Eimani; Mohammad Reza Bigdeli; Bita Ebrahimi; Abdol Hossein Shahverdi; Afsane Golkar Narenji; Reyhane Abedi (Elsevier, 2014)
Objective: Reactive oxygen species have effects on gamete quality and gamete interaction; they influence spermatozoa, oocytes, embryos, and their environment. In this study, we evaluated the antioxidant effect of different concentrations of saffron (Crocus sativus L.) aqueous extract (SAE) and its ingredient, crocin, on the improvement of in vitro maturation (IVM) and subsequent in vitro fertilization (IVF) and embryo development of mouse oocytes. Materials and methods: Cumulus oocyte complexes were collected from ovaries, and germinal vesicle oocytes were cultured in the presence of SAE and crocin. SAE was added at dosages of 5 μg/mL, 10 μg/mL, and 40 μg/mL; dosages of crocin were 50 μg/mL, 100 μg/mL, and 400 μg/mL. All dosages were added to maturation medium and a group without SAE or crocin was considered as the control group. Following IVM, metaphase II oocytes were fertilized and cultured in vitro in order to observe embryo development. Results: Both SAE and crocin improved the rate of IVM, IVF, and in vitro culture. Addition of 40 μg/mL SAE to maturation medium significantly increased the rate of IVM, IVF, and in vitro culture (p < 0.05). Furthermore 100 μg/mL crocin significantly increased the IVM rate compared to the control group (p < 0.05). Conclusion: Use of SAE during IVM can affect on IVM, IVF, and early embryo development in a dose-dependent manner. SAE appears to have a stronger effect than pure crocin.